Non-pharmacological interventions for methamphetamine use disorder: a systematic review - AshaRani, PV; Hombali, Aditi; Seow, Esmond; Ong, Wei Jie; Tan, Jit Hui; Subramaniam, Mythily (Drug and alcohol dependence, 2020)
•Non pharmacological interventions are effective in treating METH use disorder.•Contingency management and cognitive behavioural therapy yield better outcomes.•Heterogeneity noted across the studies in terms of methodology and interpretation.•The methodology should be standardised to allow comparison across the studies. Methamphetamine (METH) use is on the rise globally, with the number of treatment seekers increasing exponentially across the globe. Evidence-based therapies are needed to meet rising treatment needs. This systematic review intends to appraise the existing evidence to identify effective non-pharmaceutical approaches for the treatment of METH use disorder. Five electronic bibliographic databases-Ovid (Medline), Embase, Cumulative Index of Nursing and Allied Health Literature (CINAHL), Web of Science and PsycINFO- were searched to identify relevant studies that were published between January 1995 to February 2020. Studies were selected and assessed by two independent reviewers. A systematic review of data from both randomised control trials (RCT) and non-RCTs was conducted to appraise the evidence. A total of 44 studies were included in the review. Behavioural interventions, i.e. cognitive behavioural therapy (CBT), contingency management (CM), exercise, residential rehabilitation based therapies, repetitive transcranial magnetic stimulation (rTMS), and matrix model demonstrated treatment efficacy in promoting abstinence, reducing methamphetamine use or craving in the participants. While CM interventions showed the strongest evidence favouring the outcomes assessed, tailored CBT alone or with CM was also effective in the target population. Behavioural interventions should be considered as the first line of treatment for methamphetamine use disorder. Future studies should address the longevity of the effects, and limitations due to smaller sample sizes and high dropout rates to enable better assessment of evidence.